Alternative Life-History in Native Trout (Salmo spp.) Suppresses the Invasive Effect of Alien Trout Strains Introduced Into Streams in the Western Part of the Balkans - Škraba Jurlina, Dubravka; Marić, Ana; Mrdak, Danilo; Kanjuh, Tamara; Špelić, Ivan; Nikolić, Vera; Piria, Marina; Simonović, Predrag (Frontiers in Ecology and Evolution, 2020)
The diversity of native trout fish Salmo spp. comprises a variety of nominal taxa in Serbia, Montenegro, and Bosnia and Herzegovina. Recent mapping of the resident trout populations detected the presence of brown trout Salmo trutta (sensu stricto) of the Atlantic (AT) mtDNA lineage introduced into populations of both tentative Danubian trout Salmo labrax and of tentative Adriatic trout Salmo farioides belonging to the Danubian (DA) and Adriatic (AD) mtDNA lineages, respectively. Introduction of the tentative Macedonian trout Salmo macedonicus of the AD lineage was also detected in a native population of the tentative S. labrax. In almost all recipient nonmigratory trout populations, a cross-breeding between native and introduced trout was detected by heterozygosity in either only the LDH-C nuclear locus or the LDH-C and specific microsatellite loci. The only exception was a population where both resident and migratory, lake-dwelling individuals of the tentative Adriatic trout spawned in a downstream section of a stream in Montenegro, as no microsatellite alleles of Atlantic brown trout that had been introduced upstream were detected. The occurrence of cross-breeding between Adriatic and brown trout was evident in the isolated, upstream section. It appears that migrating, lake-dwelling Adriatic trout in combination with their resident, stream-dwelling conspecifics suppress the introgression of genes from those situated upstream. In this regard, consideration should be given to the occurrence of the migratory brown trout in the Danube River at the broader Iron Gate Gorge area. They migrate in late summer and early fall from the Iron Gate One reservoir to the lower sections of tributaries devoid of any trout fish. However, some of these streams house very special native trout of the DA lineage in their short-extending upper sections. These native trout populations are, so far, still out of contact with the reservoir-dwelling trout. However, given the resilience of trout and their migratory life history, the outcome of this introduction could be deleterious for those native fish that are very precious in the conservation sense.